Atividade anticancer do extratos brutos e das frações ativas obtidos de Piper regnellii (Miq.) C. DC. var. regnellii - Longato, Giovanna Barbarini, 1985- (2010)
Orientadores: João Ernesto de Carvalho, Mary Ann Foglio